Clickable SBA-15 mesoporous materials: synthesis, characterization and their reaction with alkynes - Malvi, Bharmana; Sarkar, Bibhas R.; Pati, Debasis; Mathew, Renny; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam (Journal of Materials Chemistry, 2009)
SBA-15 mesoporous silica has been functionalized with azidopropyl groups through both one-pot co-condensation and post-synthetic grafting. For both these methodologies, azidopropyltriethoxysilane was used to introduce the azidopropyl groups. The azidopropyl modified SBA-15 material synthesized by one-pot co-condensation had hexagonal crystallographic order, pore diameters up of 50 angstrom, and the content of azidopropyl groups was found to be 1.3 mmol g(-1). The presence of the azidopropyl group was confirmed by multinuclear ((13)C, (29)Si) solid state NMR and IR spectroscopy. Both these materials underwent very efficient Cu(I)-catalyzed azide alkyne ``click'' reaction (CuAAC) with a variety of alkynes. Nearly 85% of the azide present in the SBA-15 material was converted to the corresponding triazole when propargyl alcohol was used as the substrate. This methodology was also used to incorporate mannose into SBA-15. Incubation of this mannose labeled SBA-15 with fluorescein labeled Concanavalin-A led to the formation of a fluorescent silica-protein hybrid material. The ease of synthesis for the azide labeled SBA-15 material together with its ability to undergo very efficient chemoselective CuAAC in water would make it a very attractive platform for the development of covalently anchored catalysts, enzymes and sensors.

Controlled synthesis of O-glycopolypeptide polymers and their molecular recognition by lectins - Pati, Debasis; Shaikh, Ashif Y.; Das, Soumen; Nareddy, Pavan Kumar; Swamy, Musti J.; Hotha, Srinivas; Sen Gupta, Sayam (Biomacromolecules, 2012)
The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to be alpha-helical in aqueous solution. However, we were able to control the secondary conformation of the glycopolypeptides (alpha-helix vs nonhelical structures) by polymerizing raceznic amino acid glyco NCAs. We have also investigated the binding of the glycopolypeptide poly(alpha-manno-O-lys) with the lectin Con-A using precipitation and hemagglutination assays as well as by isothermal titration calorimetry (ITC). The ITC results clearly show that the binding process is enthalpy driven for both alpha-helical and nonhelical structures, with negative entropic contribution. Binding stoichiometry for the glycopolypeptide poly(alpha-manno-O-lys) having a nonhelical structure was slightly higher as compared to the corresponding polypeptide which adopted an alpha-helical structure.

Cationic charged helical glycopolypeptide using ring opening polymerization of 6-deoxy-6-azido-glyco-N-carboxyanhydride - Shaikh, Ashif Y.; Das, Soumen; Pati, Debasis; Dhaware, Vinita; Sen Gupta, Sayam; Hotha, Srinivas (Biomacromolecules, 2014)
Glycopolypeptides with a defined secondary structure are of significance in understanding biological phenomena. Synthetic glycopolypeptides, or polypeptides featuring pendant carbohydrate moieties, have been of particular interest in the field of tissue engineering and drug delivery. In this work, we have synthesized charged water-soluble glycopolypeptides that adopt a helical conformation in water. This was carried out by the synthesis of a glyco-N-carboxyanhydride (glyco-NCA) containing an azide group at the sixth position of the carbohydrate ring. Subsequently, the NCA was polymerized to obtain azide-containing glycopolypeptides having good control over molecular weight and polydispersity index (PDI) in high yields. We were also able to control the incorporation of the azide group by synthesizing random co-glycopolypeptide containing 6-deoxy-6-azido and regular 6-OAc functionalized glucose. This azide functionality allows for the easy attachment of a bioactive group, which could potentially enhance the biological activity of the glycopolypeptide. We were able to obtain water-soluble charged glycopolypeptides by both reducing the azide groups into amines and using CuAAC with propargylamine. These charged glycopolypeptides were shown to have a helical conformation in water. Preliminary studies showed that these charged glycopolypeptides showed good biocompatibility and were efficiently taken up by HepG2 cells.